Admission respiratory status predicts mortality in COVID‐19. Issue 5 (24th May 2021) - Chatterjee, Neal A.; Jensen, Paul N.; Harris, Andrew W.; Nguyen, Daniel D.; Huang, Henry D.; Cheng, Richard K.; Savla, Jainy J.; Larsen, Timothy R.; Gomez, Joanne Michelle D.; Du‐Fay‐de‐Lavallaz, Jeanne M.; Lemaitre, Rozenn N.; McKnight, Barbara; et al.
Abstract: COVID‐19 has significant case fatality. Glucocorticoids are the only treatment shown to improve survival, but only among patients requiring supplemental oxygen. WHO advises patients to seek medical care for "trouble breathing, " but hypoxemic patients frequently have no respiratory symptoms. Our cohort study of hospitalized COVID‐19 patients shows that respiratory symptoms are uncommon and not associated with mortality. By contrast, objective signs of respiratory compromise—oxygen saturation and respiratory rate—are associated with markedly elevated mortality. Our findings support expanding guidelines to include at‐home assessment of oxygen saturation and respiratory rate in order to expedite life‐saving treatments patients to high‐risk COVID‐19 patients.